Managerial focus of a regional vocational education and training system on the needs of socio-economic development - S. Yu. Alasheev; T. G. Kuteinitsyna; N. Yu. Postalyuk; V. A. Prudnikova (Russian State Vocational Pedagogical University, 2021)
Introduction. The policy of the European Union and many other countries in the field of education and training of personnel with applied qualifications is traditionally focused on the needs of the economy of territories and the competitiveness of enterprises. Currently, a new organisational and managerial model is being approved in the Russian Federation, related to the world practice of innovative management. Some specific management tools of the targeted focus of VET systems on the needs of the economy have repeatedly been the subject of study. However, it has not been decided yet what specific sets of management tools should be used and how to effectively achieve the dynamic balance of personnel supply and demand in regional labour markets.Aim. The present research aimed to establish the features of the targeted managerial focusing of the activities of the regional VET systems on the needs of the socio-economic development of the constituent entity of the Russian Federation.Methodology and research methods. The research methodology is based on the following principles and approaches: system- and activity-based analysis of social objects, comparative analysis and modelling of social systems. The authors applied the metrological principle to compare the obtained values of indicators/indicators of the activity of VET systems with the "standard", which is used as threshold values set by the method of expert assessments or by average values of indicators in current Russian monitoring studies. Aggregated indices were calculated as sums of normalised values of corresponding indicators groups.The following research methods were applied: questioning, expert assessment method, scaling, web analysis, content analysis of documents, methods of mathematical statistics in the processing of sociological data, methods of analysis, synthesis, generalisation, comparison, and abstraction in the interpretation of research results.The data sources were open-source databases (websites of the government of constituent entities of the Russian Federation, educational authorities, and professional educational organisations); statistical information; expert assessments of regional specialists and specialists of executive authorities in the field of education.Results and scientific novelty. As a result of the study, it was found that the management focus tools of the pilot regional VET system do not fully correspond to the needs of regionally oriented development. Regional differentiation is significant in accordance with most of the parameters, which characterise management tools for orienting the activities of the VET systems to the demands of the external environment. The spread in the values of indicators for the pilot regions reaches 80 %. According to several indicators, the identified differences are due to the different economic conditions of the regions. However, most of the parameters, which characterise the adaptability of regional VET systems, are not related to the economic component of the development of the constituent entities of the Russian Federation, and, are determined mainly by the factors of educational resources management and management models used by educational systems and individual professional educational organisations.Practical significance. The results obtained in the study make it possible to highlight the problem areas in the management of the VET system in the region and to identify reserves for enhancing the compliance of the conditions and results of the VET system and educational organisations with the needs of the socio-economic development of regions.